Charge Photogeneration and Recombination in Mesostructured CuSCN‐Nanowire/PC70BM Solar Cells. Issue 8 (2nd May 2018) - Firdaus, Yuliar; Seitkhan, Akmaral; Eisner, Flurin; Sit, Wai‐Yu; Kan, Zhipeng; Wehbe, Nimer; Balawi, Ahmed H.; Yengel, Emre; Karuthedath, Safakath; Laquai, Frédéric; Anthopoulos, Thomas D.
Abstract : Fullerene‐based materials are widely used as electron acceptors in organic bulk‐heterojunction solar cells; yet, they have rarely been used as the only photoactive component due to their low absorbance and limited charge generation efficiency. However, blending the wide‐bandgap p‐type material copper (I) thiocyanate (CuSCN) with [6, 6]‐phenyl‐C71 ‐butyric acid methyl ester (PC70 BM) leads to the formation of a unique mesostructured p‐n like heterointerface between CuSCN and PC70 BM and solar cells with a power conversion efficiency (PCE) of up to 5.4%. Here, we examine in detail the reasons for the surprisingly good device performance and elucidate the charge photogeneration and recombination mechanisms in CuSCN‐based devices with PC70 BM as the exclusive light‐absorbing material. Our studies clearly demonstrate that a substantial fraction of the photocurrent in the CuSCN‐based devices results from improved dissociation of fullerene excitons and efficient charge transfer at the CuSCN:PC70 BM interface combined with reduced geminate and nongeminate charge recombination losses. Our results have implications beyond the fullerene‐based devices studied here, as they demonstrate that careful selection of a mesostructured p‐type transparent semiconductor paves the path to a new type of efficient single photoactive material solar cells. Abstract : Efficient charge photogeneration and collection is realized in solar cells based on a mixture of copper(I)thiocyanate (CuSCN) and PC70 BM acting as the hole‐extracting and light‐absorbing materials, respectively. The study by Firdaus et al. reveals that the mesostructured p‐n heterointerface formed spontenously between CuSCN and PC70 BM facilitates efficient charge dissociation of charge‐transfer states created upon illumination. In parallel, the interface allows strictly selective charge collection prior to recombination.